Optimization of Educator Quality through Job Analysis and Personnel Planning - Da Silva, Antonius; Izzati, Ummi Anugerah; Karwanto, Karwanto (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
Optimizing the quality of educators is a crucial aspect of improving the overall quality of educational institutions. This study aims to analyze the application of human resource management (HRM) through job analysis and personnel planning strategies to address the issue of declining educator quality. This research employs a systematic literature review (SLR) method by analyzing nine relevant articles from online databases. The findings indicate that a holistic HRM approach, involving job analysis and personnel planning, can significantly enhance educator quality. Factors such as salary, professional training, workload, and recognition were also identified as triggers for low educator quality. This study suggests the need for an HRM approach tailored to the unique characteristics of each educational institution to achieve optimal results.